Characteristics, risk factors and histopathological types of bronchogenic carcinoma among cases presented to Chest Department, Al-Zahraa Hospital, Al-Azhar University - Abo-Elkheir, Omaima I.; Hafez, Manal R. (International Journal Of Community Medicine And Public Health, 2018)
Background: Recently, lung cancer representing 5-7% of all cancers in Egypt with unavailable accurate epidemiological data. This study aims to identify characteristics, risk factors and histopathological types of bronchogenic carcinoma among a group of Egyptian patients. Methods: A cross sectional study was conducted on 123 cases of histopathological confirmed bronchogenic carcinoma presented to chest diseases department, Al-Zahraa Hospital, Al-Azhar University, Egypt in the period from July 2013 to May 2017. Statistical analysis of patients’ database was done using SPSS version 17. Results: Male to female ratio was 3.2:1; the majority of cases presented in their fifth (55.3%) and sixth (29.3%) decades of life, and urban: rural residence ratio was 2.1:1. Smoking was the most significant risk factor among 93.5% of cases, among them 65.9% were current smokers, 13.0% were ex-smokers and 14.6% were passive smokers. Occupational exposure to cement dust were reported among 47.2% of cases, 16.3% were farmers, 13.0% were employees, 8.9% were house wives, 8.1% were shoe makers and 6.5% were drivers. COPD was reported among 54.5% of cases. The commonest histopathological types were squamous cell carcinoma (31.7%), adenocarcinoma (30.9%), and large cell carcinoma (26.0%). Adenocarcinoma was the predominant type among females (55.3%), passive smokers (31.6%) and non-smokers (15.8%). Conclusions: Small cell lung cancer and squamous cell carcinoma subtypes were predominant among males, active smokers and workers exposed to cement dust. Adenocarcinoma was the commonest type among females, passive smokers and non-smokers. Conduction of anti-smoking campaigns; reduction of environmental pollution with regulation of occupational exposures to cement dust are recommended.